2014
DOI: 10.1186/1472-6874-14-22
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of factors affecting mental health amongst low-income working mothers in Bangalore, India

Abstract: BackgroundLow-income urban working mothers face many challenges in their domestic, environmental, and working conditions that may affect their mental health. In India, a high prevalence of mental health disorders has been recorded in young women, but there has been little research to examine the factors that affect their mental health at home and work.MethodsThrough a primarily qualitative approach, we studied the relationship between work, caring for family, spousal support, stress relief strategies and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 33 publications
4
66
0
Order By: Relevance
“…This is in congruence with findings from various studies (Kumar et al 2005;Patel et al 2006;Shidhaye and Patel 2010). Travasso, Rajaraman, and Heymann (2014) also indicated in their qualitative study that slum women of Bangalore who had an alcoholic husband were more susceptible to severe and prolonged periods of depression and suicidal attempts. Patel et al (2006) showed that mental disorders were more frequent among women who experienced difficulty in managing financially, which is similar to our result.…”
Section: Discussionsupporting
confidence: 88%
“…This is in congruence with findings from various studies (Kumar et al 2005;Patel et al 2006;Shidhaye and Patel 2010). Travasso, Rajaraman, and Heymann (2014) also indicated in their qualitative study that slum women of Bangalore who had an alcoholic husband were more susceptible to severe and prolonged periods of depression and suicidal attempts. Patel et al (2006) showed that mental disorders were more frequent among women who experienced difficulty in managing financially, which is similar to our result.…”
Section: Discussionsupporting
confidence: 88%
“…A study conducted among working mothers by Sandra Mary Travasso et al, reported that, lack of adequate support for child care appear to be more susceptible to severe and prolonged periods of depression. 21 The finding is similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Religion has been consistently identified as a primary coping strategy for cancer patients in India (65, 66), and, like the grouping of instrumental and emotional support into our social support factor, Indian head and neck cancer patients jointly employed problem-focused and emotion-focused coping strategies (67). Both types of social support were leveraged by women with moderate to severe depression and anxiety, who reported that both social and financial support from family, friends and colleagues mitigated their mental distress (68). In contrast to the typical Western view of women as more emotion-focussed, Talukdar found that women in India engaged in problem-focused coping more frequently than men (28).…”
Section: Discussionmentioning
confidence: 99%